Humour and politics: A transcultural perspective (2019)
Humor is a universal human expression that occurs within the conventions and special features of each culture. Authors from diverse origins, times and disciplines have written treatises about laughter, comedy and the comical to establish a concept and describe humor as a distinctly human characteristic. The strength and importance of studies on humor translate into the analysis of highly significant events, such as those that occurred because of religious satire. This book will reflect on humor starting from approximations regarding its concept, its history or evolution in various contemporary expressions to offer evidence of its daily validity and “seriousness.” The introductory essay will address the effect of the humor-politics relationship, and then two sections will be presented: Graphic Humor, Politics and Religion and Social Repression and Humor. Finally, important conclusions about humor will be drawn and solutions will be proposed to different political and social problems.